âPENGARUH DISIPLIN KERJA, KEPUASAN KERJA, DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA KARYAWAN PADA PT. TELKOM REGIONAL IV JAWA TENGAH & DAERAH ISTIMEWA YOGYAKARTAâ - Sherli Junianingrum, 14.05.51.0235; Murdiyanto, Agus (Students Journal of Economic and Management, 2018)
This study aims to analyse the influence of work discipline, job statisfaction, and organizational commitment on employee performance in PT. Telkom Regional IV Jawa Tengah and Daerah Istimewa Yogyakarta.This study use three independent variable, namely work discipline, job statisfaction and organizational commitment, with the dependent variable is the performance of employees. The data in this study were collected through a questionnaire distributed to 110 employees in PT. Telkom Regional IV Jawa Tengah and Daerah Istimewa Yogyakarta. Based on the research that has been done shows that work discipline, job statisfaction and organizational commitment has a positive and significant impact on employee performance.Keywork discipline, job statisfaction, organizational commitment, employee performance